The Urgency and Practice of Governance And Accountability in Islamic Boarding School: Principal and Accountant Perception - Mita Tarmiati; Febriani, Dewi (Tazkia Islamic University College, 2024)
Governance and accountability play an important role in supporting sustainability in Islamic Boarding Schools. This study aims to explore governance and accountability in Islamic Boarding Schools both in terms of urgency and practice obtained from the perceptions of Islamic Boarding School principals and accountants. In addition, this study aims to compare the urgency and practice of governance and accountability in Islamic Boarding Schools whose finances are independent of Islamic Boarding Schools whose finances come from donations, as well as Islamic Boarding Schools under the auspices of organizations with Islamic Boarding Schools that stand independently. This study is a quantitative study with descriptive and comparative analysis. The findings of this study indicate that governance and accountability are considered very important in Islamic Boarding Schools according to the perceptions of the principals, and from the perspective accountants regarding the practice of governance and accountability, this has begun to be implemented effectively even though it is still not consistently implemented by Islamic Boarding Schools, such as the lack of financial reports presented by Islamic Boarding Schools and incomplete by existing regulations. In addition, the results of the difference test show that there is no significant difference regarding governance and accountability between the groups of Islamic Boarding Schools tested both in terms of urgency and practice.